Endogenous Derivation of Optimal Environmental Policies for Proper Treatment of Stockbreeding Wastes in the Upstream Region of Miyun Reservoir, Beijing - Jingjing Yan; Feng Xu; Takeshi Mizunoya; Huanzheng Du; Xuebo Zhan; Yoshiro Higano (European Regional Science Association (ERSA), 2010)
Stockbreeding industries are increasing rapidly in rural areas around big cities in China, especially the rural areas around Beijing. This increase carries high risks to the environment due to emissions of large amounts of pollutants in terms of COD (chemical oxygen demand), T-N (total nitrogen) and T-P (total phosphorus) as well as greenhouse gases to rivers and the atmosphere. On the other hand, stockbreeding wastes are a typical biomass resource and can be used as an energy source by advanced new technologies. In this study, we selected Miyun County of Beijing and focused on analyzing the synthetic environmental management policies by computer simulation including the introduction of two new technologies to improve the environment and provide more biomass energy. The model considered both the total ecological system of the objective region and the social-economic situational changes during a ten year period from 2007 to 2016. The basic aim of this article has been to develop a dynamic liner model, and to verify it through carrying out simulations in order to evaluate the possibility and feasibility to introduce new technologies into rural areas around big cities in China and research the arrangement of the new technologies to realize effective utilization of stockbreeding biomass resource. When we adopted the policy to introduce two new technologies, the policy was a very effective tool to reduce environmental pollutants in all simulations. The introduction of two new technologies raised the level of economic growth by 10% as compared to not adopting the new technologies policy. When the two new technologies were introduced, the objective value (total T-N) showed a reduction of about 13% as compared to not adopting the new technologies. The purpose of our research is to establish effective utilization methods for biomass resources as well as coordinate resource reutilization, environmental preservation and economic development, and finally realize sustainable development of the society.
Keywords: 330; Environmental policy; Regional development; Biomass resource; Modeling; Simulation